(untitled) (Fiep Bulletin - online, 2014)
There is an ambiguity in approaches to application of individual test issues within the primary school age. In order to identify the substance of a complex of motor abilities not only the information on specific elements is important but also on mutual relations between them and their structure. The aim of the study was to define a factor model of motor and physical indicators in primary school children. This model could be applied as a tool for defining valid, reliable, and feasible diagnostic methods within the elementary physical education context. Test battery consisted of items indicating of condition and coordination abilities. 382 8-year-old children participated in the research, 190 boys. Tested children were randomly selected from 12 primary schools in the East Region of the Slovak Republic. In both examined groups boys and girls the factor model consisted of similar factors saturated by power, speed, and coordination, and physical indicators with a great share on the whole variance. The results show on a necessity to apply a multidimensional approach to motor performance diagnostics in primary school children. Knowledge about the dimensionality of motor performance ability should be critical for further research, as well as for selection valid, reliable, and feasible diagnostic methods.